2019
DOI: 10.1002/adfm.201907145
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid 3D Printing of Synthetic and Cell‐Laden Bioinks for Shape Retaining Soft Tissue Grafts

Abstract: Despite recent advances in clinical procedures, the repair of soft tissue remains a reconstructive challenge. Current technologies such as synthetic implants and dermal flap autografting result in inefficient shape retention and unpredictable aesthetic outcomes. 3D printing, however, can be leveraged to produce superior soft tissue grafts that allow enhanced host integration and volume retention. Here, a novel dual bioink 3D printing strategy is presented that utilizes synthetic and natural materials to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Naturally derived polymers such as alginate, fibrin, HA, collagen, and gelatin are highly printable using extrusion-based bioprinting. They offer a low donor-site morbidity and invoke a low immune response [ 88 ]. However, in vivo, they often undergo rapid degradation and/or remodeling which decreases their mechanical stability and fidelity over time.…”
Section: Bioink Requirementsmentioning
confidence: 99%
“…Naturally derived polymers such as alginate, fibrin, HA, collagen, and gelatin are highly printable using extrusion-based bioprinting. They offer a low donor-site morbidity and invoke a low immune response [ 88 ]. However, in vivo, they often undergo rapid degradation and/or remodeling which decreases their mechanical stability and fidelity over time.…”
Section: Bioink Requirementsmentioning
confidence: 99%
“…It has been reported that 3D printing can be an ideal approach to fabricate various micro/macroscale intricate structures owing to its outstanding repeatability and reproducibility which is assisted by a computer-aided method. This emerging technology has started a new era of designing and manufacturing of tissue engineering cell-laden substitutes and biological constructs [ 25 , 26 ]. In this study, CPC scaffolds with interconnected pores (diameter 5 mm, thickness 2 mm) printed using calcium phosphate semi-solid paste (α-tricalcium phosphate and calcium-deficient hydroxyapatite) exhibited rough surface morphology which could be attributed to the microcrystalline morphology of the CPC.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the type of plastic molten wax can easily produce the desired object [20]. And the use of software that can be used for 3d printers is already present as software that is capable of producing shapes with the concept of 3 axes (x, y, z) or, in other words displaying data in 3D format [21].…”
Section: Aspects In a 3d Printermentioning
confidence: 99%